Eksistensi Hak Gadai Tanah Sawah di Desa Ubung Kecamatan Jonggat Kabupaten Lombok Tengah Nusa Tenggara Barat - I Made Adi Karsa; Ida Ayu Putu Widiati; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2020)
The issuance of Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles on September 24, 1960, then abolished the old agrarian law. The purpose of this study is to analyze the implementation of land pawns in the Ubung village, Jonggat sub-district and find out the inhibiting factors of the implementation of agricultural land pawns in Ubung Village, Jonggat District, Central Lombok Regency, West Nusa Tenggara based on Law No. 56 Prp of 1960. The method in this study is Empirical research methods and problem approaches using legal sociology. The results showed that the agricultural land pawn given by the pawnbroker and the pawn recipient was not in accordance with the law. Agricultural pawn in the community of Ubung Village, Jonggat Subdistrict, Central Lombok Regency is not in line with the agricultural land pawning regulated in Law Number 56 Prp of 1960. Factors that inhibit the implementation of agricultural pawn in Ubung Village, Jonggat Subdistrict, Central Lombok Regency NTB based on article 7 paragraph (1) and paragraph (2) of Law Number 56 Prp of 1960 ineffective are a) there has been no socialization of Law Number 56 prp of 1960 governing the problem of pawning agricultural land in Ubung Village, Jonggat District, Central Lombok Regency, NTB from the authorities. b) The culture of Ubung Village, Jonggat Subdistrict, Central Lombok Regency, NTB, which considers the provisions of Law Number 56 prp of 1960 to be incompatible with the customs contained in their environment.